Der "pfäffische Ort": Darstellung und Funktion des westfälischen Marienwallfahrtsortes Telgte in Günter Grass' Erzählung "Das Treffen in Telgte" (1979) - Garske, Volker (www.theologie-und-literatur.de (wissenschaftliche Beiträge online 2011))

Energie sparen mit Gas - Schlüter, Alexander; Rommel, Benjamin; Schäfer, Mirko; Hesselbach, Jens (energy 2.0)

Senkung des Energiebedarfs in der Produktion durch thermische Prozess- und Maschinensimulation - Schlüter, Alexander; Schäfer, Mirko; Wagner, Johannes; Schrodt, Alexander; Hesselbach, Jens (ZWF - Zeitschrift für wissenschaftliche Fabrikbetriebe)

Energy Efficiency in Industrial Processes, Talk - Schlüter, Alexander

Dem Energiefresser auf der Spur - Energetische Simulation zur Effizienzsteigerung in der Produktion - Schlüter, Alexander; Schäfer, Mirko; Hesselbach, Jens; Schmidt, Christoph (cci - Clima Commerce International)

Ungenutzte Potenziale nutzen - Auslegung und Steuerung von Energieverbundsystemen - Schlüter, Alexander; Pfaffenbach, Ottmar; Hesselbach, Jens (BWK)

Erstellung der Fallstudie Deutschland für: European Centre for the development of vocational training (CEDEFOP) (2011) - Lippegaus, Petra (Assuring quality in vocational education and training. The role of accrediting VET providers)

Assistierte Ausbildung - ein Zukunftsmodell. Das Projekt "carpo"als Beispiel guter Praxis Praxisbericht auf dem Portal überaus des Bundesinstituts für Berufsbildung - Lippegaus, Petra

Das Inklusionskonzept bringt Bewegung in die Benachteiligtenförderung - Lippegaus, Petra (Berufsbildung in Wissenschaft und Praxis (bwp) Heft 2/2011)

Walking On Broken Mesh: Defect‐Tolerant Geodesic Distances and Parameterizations - Campen, Marcel; Kobbelt, Leif (Computer Graphics Forum)
Abstract Efficient methods to compute intrinsic distances and geodesic paths have been presented for various types of surface representations, most importantly polygon meshes. These meshes are usually assumed to be well‐structured and manifold. In practice, however, they often contain defects like holes, gaps, degeneracies, non‐manifold configurations – or they might even be just a soup of polygons. The task of repairing these defects is computationally complex and in many cases exhibits various ambiguities demanding tedious manual efforts. We present a computational framework that enables the computation of meaningful approximate intrinsic distances and geodesic paths on raw meshes in a way which is tolerant to such defects. Holes and gaps are bridged up to a user‐specified tolerance threshold such that distances can be computed plausibly even across multiple connected components of inconsistent meshes. Further, we show ways to locally parameterize a surface based on geodesic distance fields, easily facilitating the application of textures and decals on raw meshes. We do all this without explicitly repairing the input, thereby avoiding the costly additional efforts. In order to enable broad applicability we provide details on two implementation variants, one optimized for performance, the other optimized for memory efficiency. Using the presented framework many applications can readily be extended to deal with imperfect meshes. Since we abstract from the input applicability is not even limited to meshes, other representations can be handled as well.

Von Diana zu Minerva. Philosophierende Aristokratinnen des 17. und 18. Jahrhunderts und ihre Netzwerke

Rezension zu: „Essen und Trinken in der Bibel” - Bergmann, Claudia Dorit (Theologie der Gegenwart)

Altered electrocortical brain activity after ACL reconstruction during force control - Baumeister, Jochen; Reinecke, Kirsten; Schubert, Michael; Weiß, Michael (Journal of Orthopaedic Research)
Abstract Afferent proprioceptive information from the knee joint may be altered due to a reconstruction of the anterior cruciate ligament (ACL), which could result in changes of cortical activity. The aim of the study is to look if force sensation and cortical activation measured by EEG are influenced by an ACL‐reconstruction when performing a force reproduction task. Nine patients after ACL reconstruction and nine healthy controls were asked to reproduce 50% of their maximal voluntary isometric contraction (MVIC) reproduction. EEG power values related to frequency bands and the error in reproduction were collected while performing the force reproduction. The aberration error demonstrated no significant differences between groups. The cortical activity results in significant higher frontal Theta power during the force reproduction task with the reconstructed limb (F3 and Fz: p < 0.05) of the ACL group compared to the controls. The EEG was able to measure changes in electrocortical activity after ACL‐reconstruction in force reproduction, whereas performance data was not affected. The results were discussed in terms of differences in attentional control with involvement of the anterior cingulate cortex related to higher frontal Theta power in the ACL patients. © 2011 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 29: 1383–1389, 2011

From Lab to Field Conditions: A Pilot Study on EEG Methodology in Applied Sports Sciences - Reinecke, Kirsten; Cordes, Marjolijn; Lerch, Christiane; Koutsandréou, Flora; Schubert, Michael; Weiss, Michael; Baumeister, Jochen (Applied Psychophysiology and Biofeedback)

Effects of induced fatigue on brain activity during sensorimotor control - Baumeister, Jochen; Reinecke, Kirsten; Schubert, Michael; Schade, Johannes; Weiss, Michael (European Journal of Applied Physiology)

Limb versus speech motor control: A conceptual review - Grimme, Britta; Fuchs, Susanne; Perrier, Pascal; Schöner, Gregor (Motor control)

Lernprozesse professionell begleiten. Beiträge des Paderborner Grundschultages 2009 zu Diagnose und Förderung

Purchase Orders of Military Garments from Papyri of Roman Egypt - Droß-Krüpe, Kerstin (Wearing the Cloak. Dressing the Soldier in Roman Times)

Wolle – Weber – Wirtschaft. Die Textilproduktion der römischen Kaiserzeit im Spiegel der papyrologischen Überlieferung - Droß-Krüpe, Kerstin

Adverse selection, investor experience and security choice in venture capital finance: evidence from Germany - Hartmann-Wendels, Thomas; Keienburg, Georg; Sievers, Sönke (European Financial Management (VHB-JOURQUAL 4 Ranking B))
This article analyses 336 German venture capital transactions from 1990 to 2005 and seeks to determine why selected financial securities differ across deals. We find that a broad array of financial instruments is used, covering straight equity, mezzanine and debt‐like securities. Based on the chosen financial securities’ upside potential and downside protection characteristics, we provide an explanation for the differing use of these securities. Our results show that investors’ deal experience, adverse selection risks and economic prospects in the public equity market influence the selection of financial securities.
Keywords: venture capital; capital structure; contract theory; deal experience